Suicidal hanging donors for lung transplantation: Is this chapter still closed? Midterm experience from a single center in United Kingdom. Issue 14 (April 2018) - Ananiadou, Olga; Schmack, Bastian; Zych, Bartlomiej; Sabashnikov, Anton; Garcia-Saez, Diana; Mohite, Prashant; Weymann, Alexander; Mansur, Ashham; Zeriouh, Mohamed; Marczin, Nandor; De Robertis, Fabio; Simon, Andre Rüdiger; et al.
Abstract : Abstract: In the context of limited donor pool in cardiothoracic transplantation, utilization of organs from high risk donors, such as suicidal hanging donors, while ensuring safety, is under consideration. We sought to evaluate the outcomes of lung transplantations (LTx) that use organs from this group. Between January 2011 and December 2015, 265 LTx were performed at our center. Twenty-two recipients received lungs from donors after suicidal hanging (group 1). The remaining 243 transplantations were used as a control (group 2). Analysis of recipient and donor characteristics as well as outcomes was performed. No statistically significant difference was found in the donor characteristics between analyzed groups, except for higher incidence of cardiac arrest, younger age and smoking history of hanging donors ( P <  .001, P =  .022 and P =  .0042, respectively). Recipient preoperative and perioperative characteristics were comparable. Postoperatively in group 1 there was a higher incidence of extracorporeal life support (27.3 vs 9.1%, P =  .019). There were no significant differences in chronic lung allograft dysfunction-free survival between group 1 and 2: 92.3 vs 94% at 1 year and 65.9 vs 75.5% at 3 years ( P =  .99). The estimated cumulative survival rate was also similar between groups: 68.2 vs 83.2% at 1 year and 68.2% versus 72% at 3 years ( P =  .3758). Hanging as a donor cause of death is not associated with poor mid-term survival or chronic lung allograft dysfunction following transplantation. These results encourage assessment of lungs from hanging donors, and their consideration for transplantation.